Implementasi Program Literasi Melalui Pemberian Bingo Card Untuk Menumbuhkan Minat Baca Pada Siswa Kelas III SDN Selorejo II - Oktaviani, Rizka; Liyah Agustinah, Evi Saraswati (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this study to (1) describe the implementation of literacy programs by giving a bingo card to develop a reading interest in class III SDN Selorejo II, (2) describe interest in student III SDN Selorejo after a bingo card. The study uses qualitative approach research procedures with descriptive types of qualitative research. This research’s data and data covers primary and secondary data sources. The data-collecting techniques used were interviews, questionnaires, and documentaries. The data analysis techniques performed in this study through data reduction, data presentation, deduction drawing. The validity of data testing techniques ran through triangulation, and surveillance persistence. Research results entitled show that; (1) implementation of literacy programs through a bingo card to develop a reading interest in class III SDN Selorejo II, done on a three-stage basis; (a) the breeding stage, done by having student do with a 15-minute lesson from various media; (b) the development stage, made through a gift of bingo cards that scented students select question cards that read B, I, N, G, O in the available pouch; (c) the learning stage, students work on the questions on the cards that have been drawn. Students win prizes when they gather the letter B, I, N, G, O. (2) interest in reading students after a bingo card, it is known to experience considerable growth. This is evident from what students did not want to read to want to do a reading activity up to 3-4 story titles because of the challenge on the bingo card.